The Biological Standard of Living in the two Germanies - John Komlos; Peter Kriwy (Ludwig-Maximilians-Universität München, Volkswirtschaftliche Fakultät, 2003)
Physical stature is used as a proxy for the biological standard of living in the two Germanies before and after unification in an analysis of a cross-sectional sample (1998) of adult heights, as well as among military recruits of the 1990s. West Germans tended to be taller than East Germans throughout the period under consideration. Contrary to official proclamations of a classless society, there were substantial social differences in physical stature in East-Germany. Social differences in height were greater in the East among females, and less among males than in the West. The difficulties experienced by the East-German population after 1961 is evident in the increase in social inequality of physical stature thereafter, as well as in the increasing gap relative to the height of the West-German population. After unification, however, there is a tendency for East-German males, but not of females, to catch up with their West-German counterparts.
urn:nbn:de:bvb:19-epub-55-0
Keywords: I31; 330; living standards; welfare; socialism; capitalism; transformation; height; social inequality